Facies and bed type analysis of a thin-bed dominated turbidite succession in the Miocene Temburong formation, Kampung Bebuloh, Labuan, Malaysia / Farah Syafira Burhanuddin - Farah Syafira , Burhanuddin (2023)
Thin-bedded turbidites are important hydrocarbon-bearing reservoirs in many mature fields throughout the world. The type of turbidite depositional setting strongly influences reservoir vertical and horizontal continuity. However, differentiation between lobe and levee associated thin-bedded turbidites is still challenging because of the generally similar facies characteristics. This study aims to solve this problem by conducting a detailed bedscale facies and bed-type analysis on the Early Miocene Temburong Formation exposed at Kampung Bebuloh, Labuan, Malaysia, which may uncover features that can help in differentiating both depositional types. Six bed types are recognised in the Temburong Formation, which are interpreted as low density turbidites (BT1 – 4), hybrid event beds (BT 5), sustained turbidites (BT6) and possible densite muds (some BT3). Detailed facies and ichnology analysis reveal features which are consistent with a lobe fringe deposit rather than levee-associated environment interpretation, including tabular bed geometries, presence of hybrid event beds, and the absence of thick-bedded channel-fill sandstones. Five bed type associations are identified and interpreted as representing subenvironments within an overall lobe depositional setting. A diverse trace fossil assemblage, comprising the Nereites ichnofacies is consistent with a deep marine environment. Further identification of the Paleodictyon and Nereites sub-ichnofacies indicates a distal turbidite system setting, most likely lobe fringe. Based on the thick accumulation of FA2 and FA3 and no distinct observable vertical trend, the Early Miocene Temburong Formation in Labuan is interpreted as turbidites deposited at the fringes of lobe complexes rather than a single lobe fringe. Earlier works into the Temburong Formation in SW Labuan propose a middle slope to proximal basin floor setting where the thin-bedded intervals were interpreted as potentially representing either levee deposits or the fringes of confined lobe deposits. Conversely, the Temburong Formation at Kampung Bebuloh exhibits characteristics of an unconfined lobe setting, suggesting an evolutionary change in depositional conditions over time.